Gut bacteria Prevotellaceae related lithocholic acid metabolism promotes colonic inflammation - Liping Chen; Zhenghao Ye; Junhua Li; Lijia Wang; Yu Chen; Meiping Yu; Jian Han; Jiangeng Huang; Dongyan Li; Yongling Lv; Kai Xiong; De’an Tian; et al. (Journal of Translational Medicine)
Abstract Background The conversion of primary bile acids to secondary bile acids by the gut microbiota has been implicated in colonic inflammation. This study investigated the role of gut microbiota related bile acid metabolism in colonic inflammation in both patients with inflammatory bowel disease (IBD) and a murine model of dextran sulfate sodium (DSS)-induced colitis. Methods Bile acids in fecal samples from patients with IBD and DSS-induced colitis mice, with and without antibiotic treatment, were analyzed using ultraperformance liquid chromatography-mass spectrometry (UPLC-MS). The composition of the microbiota in fecal samples from IBD patients and DSS-colitis mice was characterized via Illumina MiSeq sequencing of the bacterial 16S rRNA gene V3-V4 region. Metagenomic profiling further identified metabolism-related gene signatures in stool samples from DSS-colitis mice. Histological analysis, quantitative PCR (qPCR) and Western Blotting were conducted on colonic samples from DSS-induced colitis mice to assess colonic inflammation, mucosal barrier integrity, and associated signaling pathways. The multivariate analysis of bile acids was conducted using Soft Independent Modelling of Class Analogy (SIMCA, Umetrics, Sweden). The relation between the relative abundance of specific phyla/genera and bile acid concentration was assess through Spearman's correlation analyses. Finally, lithocholic acid (LCA), the key bile acid, was administered via gavage to evaluate its effect on colonic inflammation and mucosal barrier integrity. Results In patients with IBD, the composition of colonic bile acids and gut microbiota was altered. Moreover, changes in the gut microbiota further modulate the composition of bile acids in the intestine. As the gut microbiota continues to shift, the bile acid profile undergoes additional alterations. The aforementioned alterations were also observed in mice with DSS-induced colitis. The study revealed a correlation between dysbiosis of the gut microbiota and modifications in the profile of colonic bile acids, notably LCA observed in both patients with IBD and mice with DSS-induced colitis. Through multivariate analysis, LCA was identified as the key bile acid that significantly affects colonic inflammation and the integrity of mucosal barrier. Subsequent experiments confirmed that LCA supplementation effectively mitigated the inhibitory effects of gut microbiota on colitis progression in mice, primarily through the activation of the sphingosine-1-phosphate receptor 2 (S1PR2)/NF-κB p65 signaling pathway. Analysis of the microbiome and metagenomic data revealed changes in the gut microbiota, notably an increased abundance of an unclassified genus within the family Prevotellaceae in DSS-induced colitis mice. Furthermore, a positive correlation was observed between the relative abundance of Prevotellaceae and bile acid biosynthesis pathways, as well as colonic LCA level. Conclusions These findings suggest that LCA and its positively correlated gut bacteria, Prevotellaceae, are closely associated with intestinal inflammation. Targeting colonic inflammation may involve inhibiting LCA and members of the Prevotellaceae family as potential therapeutic strategies.